Factor Analysis of Physical Conditions Determinants of Ability Smash Salto Sepak Takraw: Analisis Kondisi Fisik Faktor Penentu Kemampuan Smash Salto Sepak Takraw - Hermawan, Henry; Purnama, Sapta Kunta; Nugroho, Haris (Procedia of Social Sciences and Humanities, 2022)
The purpose of this study was to determine the factors of physical condition that determine the ability of the sepaktakraw somersault smash. This research method uses a quantitative approach with a confirmatory factor analysis design. The data to be collected will be processed and analyzed using the Computerized Statistics Program with the SPSS (Statistical Product and Service Solutions) version 23 system and using the Kaiser-Meyer-Olkin and Barlett's Test. The population in this study were all male sepak takraw athletes from Central Java in the smash position, totaling 73 athletes. The sampling technique used was purposive random sampling as many as 15 athletes. Based on the results of the research and data analysis that has been carried out, it can be concluded that the dominant physical condition factors that determine the ability of the sepak takraw somersault are speed, agility and leg muscle power.